2018
DOI: 10.5946/ce.2018.132
|View full text |Cite
|
Sign up to set email alerts
|

Linked Color Imaging and Blue Laser Imaging for Upper Gastrointestinal Screening

Abstract: White light imaging (WLI) may not reveal early upper gastrointestinal cancers. Linked color imaging (LCI) produces bright images in the distant view and is performed for the same screening indications as WLI. LCI and blue laser imaging (BLI) provide excellent visibility of gastric cancers in high color contrast with respect to the surrounding tissue. The characteristic purple and green color of metaplasias on LCI and BLI, respectively, serve to increase the contrast while visualizing gastric cancers regardless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 44 publications
0
89
0
Order By: Relevance
“…Some recent studies have reported that LCI is significantly useful for the diagnosis of active HP infection or gastric metaplasia . However, the endoscopic diagnosis of HP infection does not have objective indicators, and the diagnostic ability differs between doctors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent studies have reported that LCI is significantly useful for the diagnosis of active HP infection or gastric metaplasia . However, the endoscopic diagnosis of HP infection does not have objective indicators, and the diagnostic ability differs between doctors.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies have reported that LCI is significantly useful for the diagnosis of active HP infection or gastric metaplasia. 7,8 However, the endoscopic diagnosis of HP infection does not have objective indicators, and the diagnostic ability differs between doctors. Therefore, it is necessary to establish interpretable universal methods for an endoscopic diagnosis of an HP infection, such as a computer-aided diagnosis (CAD).…”
Section: Introductionmentioning
confidence: 99%
“…7 An overview of these two techniques (BLI and LCI) highlighting their respective value for the color-based recognition of early gastric cancers was also published. 8 The characteristic purple and green color of metaplasia on LCI and BLI, respectively, serves to increase the contrast allowing the diagnosis of inflamed mucosae including erosions and early gastric cancer.…”
mentioning
confidence: 99%
“…LCI and BLI have high emission intensity of short wavelengths that reflect from the mucosal surface. 18 This histological difference may influence the spectral reflectance of both epithelia even after iodine staining, which results in different colors.…”
Section: Discussionmentioning
confidence: 99%